2002
DOI: 10.1179/146580102225001418
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties and recyclability of thermoplastic elastomer composites of white rice husk ash-ethylene/propylene/diene terpolymer-polypropylene

Abstract: Rice husk, which is usually regarded as an agricultural waste, when burnt produces a silica rich ash known as white rice husk ash (WRHA). This low cost and environmental friendly ller derived from a renewable source has been incorporated into an elastomer rich ethylene/propylene/diene terpolymer (EPDM)-polypropylene (PP) matrix to prepare thermoplastic elastomer composites, by melt mixing in a Brabender plasticorder. Elastomer components of the composites were dynamically cured in the presence of WRHA. Mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…International Journal of Polymer Science 5 Table 4: Volume fraction of EPDM due to swelling in Chloroform. where V ro is the volume fraction of rubber in the unfilled vulcanizates, V r f is the volume fraction of rubber in the filled vulcanizates, φ is the volume fraction of the filler, and c is the constant characteristic of the filler which indicates the degree of adhesion [22][23][24][25][26][27][28][29][30].…”
Section: Effect Of Fiber Loading On the Swelling Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…International Journal of Polymer Science 5 Table 4: Volume fraction of EPDM due to swelling in Chloroform. where V ro is the volume fraction of rubber in the unfilled vulcanizates, V r f is the volume fraction of rubber in the filled vulcanizates, φ is the volume fraction of the filler, and c is the constant characteristic of the filler which indicates the degree of adhesion [22][23][24][25][26][27][28][29][30].…”
Section: Effect Of Fiber Loading On the Swelling Measurementsmentioning
confidence: 99%
“…They had indicated that the incorporation of natural fibers into polymers could improve some desired properties. However, less attention has been paid to the incorporation of natural fibers to form elastomeric composites [21][22][23][24][25][26][27][28][29][30]. These composites exhibit combined behavior of the soft, elastic rubber matrix, and the stiff strong fibrous reinforcement.…”
Section: Introductionmentioning
confidence: 99%
“…Although a large number of published papers exists on PP/RH composites [7–14], and the use of white rice husk ash (WRHA) and black rice husk ash (BRHA) in plastics [15–29], there was no work reported on the use of recycled acrylonitrile‐butadiene rubber (NBRr) in PP in the presence of RHP filler. The objective of this work was to explore the mechanical properties, swelling behavior, and water absorption capacity of PP/NBRr/RHP composites.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon black (CB), silica, and clay are the classical examples. Many investigations on EPDM blends have been carried out to study the effects of CB,2–17 silica,13, 18–24 clay,25–27 and white rice husk ash (WRHA)28, 29 on the electrical properties and the curing characteristics as well as the physical properties of the filled EPDM. These research efforts are briefly reviewed below.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical properties, recyclability, and curing behavior of WRHA‐ and silica‐filled EPDM/PP thermoplastic elastomers at loadings up to 50 phr were compared 27, 28. The curing rate was increased with increasing WRHA loading, whereas the opposite trend was observed for silica‐filled vulcanizates.…”
Section: Introductionmentioning
confidence: 99%